2013
DOI: 10.5539/jas.v5n2p213
|View full text |Cite
|
Sign up to set email alerts
|

Combining Ability Analysis for Yield and Quality Traits in Tomato (Solanum lycopersicum L.)

Abstract: Thirteen parental lines were crossed in line X tester fashion comprising 10 lines and 3 testers at vegetable farm Banaras Hindu University Varanasi to estimate combining ability in tomato for fruit yield, yield components and fruit quality traits. F1 and parents were grown in towards four and half meters in randomized block design with three replications during winter-2010 involvement of both additive and non additive gene action was operated for the control of fruits per plant, fruit weight and ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

30
20
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 4 publications
30
20
1
Order By: Relevance
“…Similar findings were also reported by Kapur et al, (2013) for days to 50 per cent flowering and harvest duration; by Kumari and Sharma (2012) for number of fruits per cluster and fruit yield per plant; by Saeed et al, (2014) for number of marketable fruits per plant; by Kumar et al, (2015) for average fruit weight, number of locules per fruit and pericarp thickness; by Saleem et al, (2013) for plant height and days to marketable maturity; by Kumar et al, (2013) for ascorbic acid content. Therefore, for improving these traits, heterosis breeding will be most practical.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Similar findings were also reported by Kapur et al, (2013) for days to 50 per cent flowering and harvest duration; by Kumari and Sharma (2012) for number of fruits per cluster and fruit yield per plant; by Saeed et al, (2014) for number of marketable fruits per plant; by Kumar et al, (2015) for average fruit weight, number of locules per fruit and pericarp thickness; by Saleem et al, (2013) for plant height and days to marketable maturity; by Kumar et al, (2013) for ascorbic acid content. Therefore, for improving these traits, heterosis breeding will be most practical.…”
Section: Resultssupporting
confidence: 79%
“…Our result contradicted with the finding of Kumar et al, (2015), who reported non-additive gene action for total soluble solids content. Moreover, our results indicated dominant gene action for Alternaria resistance.…”
Section: Resultscontrasting
confidence: 57%
See 1 more Smart Citation
“…The estimates of general combining ability (gca) and specific combining ability (sca) variances and their ratio of (δ 2 gca/δ 2 sca) was less than unity for all characters studied in present investigation, which indicates that preponderance of nonadditive type of gene action. These findings are in general agreements with those of Seboka et al, (2009), Singh et al, (2012, Bhaghyalaxmi et al, (2015) and Kumar and Kerkhi (2015).…”
Section: Resultssupporting
confidence: 90%
“…Not many findings were available on the genetic control of post harvest fruit quality traits and leaf curl disease severity in tomato. The importance of non-additive gene action for the conditioning of fruit weight (Shende et al, 2012), TSS (Chattopadhyay et al, 2011), fruit acidity (Chattopadhyay et al, 2011), vitamin C content of fruit (Kumar et al, 2013), lycopene content of fruit and percent disease index (PDI) of ToLCV disease (Dharmatti et al, 2004), and fruit yield plant -1 (Shende et al, 2012;Sherpa et al, 2014) have also earlier been reported. The equal importance of both additive and non-additive gene actions for the control of polar diameter of fruit (Hazra and Nath, 2008), equatorial diameter of fruit and locules fruit -1 (Mondal et al, 2009) have also been documented.…”
Section: Resultsmentioning
confidence: 99%